Aplicaciones ofimáticas que utilizan los docentes en el proceso de enseñanza-aprendizaje en la Unidad Educativa Fiscomisional Manuel Ignacio Monteros Valdivieso. Año lectivo 2022-2023. - Chocho Valarezo., Miguel Angel (2023)
This Curricular Integration Study focuses on a research within the field of Informatics Pedagogy, likewise, it provides a contribution in the area of office automation applied in education, considering that this technology has several functionalities that allow pedagogues to manage, organize and innovate the teaching-learning process, since there is currently a wide range of platforms that provide these services. This study aims to analyze the office automation applications used by teachers in the teaching-learning process at the Unidad Educativa Fiscomisional Manuel Ignacio Monteros Valdivieso in the school year 2022-2023. This research is based on the deductive method, with a quantitative approach and an exploratory-descriptive scope, the population analyzed consisted of 46 teachers, taking a sample of 35 participants corresponding to all levels of education offered by the educational institution. For gathering relevant information, a structured questionnaire was elaborated with information supported by authors and official platforms of Microsoft 365 and Google, and the survey technique was used for its application. Consequently, the results revealed that there are 10 applications that can be used in educational environments, in addition to the applications analyzed in the study it was possible to identify that two-word processing applications are always used by teachers. Accordingly, it is recommended that the educational authors (authorities and teachers) manage training courses in order to strengthen the use of office applications in their professional work. Keywords: Applications, learning, office automation, teaching.